2017
DOI: 10.1063/1.4997013
|View full text |Cite
|
Sign up to set email alerts
|

Topological spin dynamics in cubic FeGe near room temperature

Abstract: Understanding spin-wave dynamics in chiral magnets is a key step for the development of highspeed, spin-wave based spintronic devices that take advantage of chiral and topological spin textures for their operation. Here we present an experimental and theoretical study of spin-wave dynamics in a cubic B20 FeGe single crystal. Using the combination of waveguide microwave absorption spectroscopy (MAS), micromagnetic simulations, and analytical theory, we identify the resonance dynamics in all magnetic phases (fie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
(103 reference statements)
4
18
0
Order By: Relevance
“…During the last years, the precursor states of noncentrosymmetric ferromagnets have been investigated experimentally and theoretically [14][15][16][17][18][19][20][21][22][23]. Particularly, the recent observations in bulk cubic helimagnets MnSi [18] and FeGe [16][17][18] are consistent with the crossover effects of skyrmionic states theoretically described in [9][10][11] and earlier reported in a cubic helimagnet FeGe [10,11].…”
Section: Introductionsupporting
confidence: 76%
“…During the last years, the precursor states of noncentrosymmetric ferromagnets have been investigated experimentally and theoretically [14][15][16][17][18][19][20][21][22][23]. Particularly, the recent observations in bulk cubic helimagnets MnSi [18] and FeGe [16][17][18] are consistent with the crossover effects of skyrmionic states theoretically described in [9][10][11] and earlier reported in a cubic helimagnet FeGe [10,11].…”
Section: Introductionsupporting
confidence: 76%
“…H A indicates the transition to the well-established skyrmion phase in FeGe and H x marks the transition into the paramagnetic state determined by a fluctuation-disorder regime [15]. The measured phase diagram is in good agreement with literature [16][17][18][19][20][21], representing the basis for our magnetic relaxation investigations.…”
Section: Introductionsupporting
confidence: 84%
“…Recently, two bulk crystalline materials have been shown by Lorentz Transmission Electron Microscopy (LTEM) and Small Angle Neutron Scattering (SANS) to have a skyrmions lattice near or at room temperature: Co x -Zn y -Mn z alloys 38 , 39 , and stoichiometric cubic FeGe 10 , 37 , 40 – 42 . In FeGe, magnetisation 43 , specific heat measurements 44 , and microwave absorption spectroscopy 45 also identified several magnetic phases compatible with skyrmions. Transport studies in FeGe thin films 26 – 30 reported an extraordinarily large Hall signature (up to 1000 n .cm in 36 nm thin films) that occurs in an “extended” phase spanning from cryogenic temperatures to the NĂ©el temperature.…”
Section: Introductionmentioning
confidence: 87%